Who believes the novel coronavirus conspiracy theories? - Gemenis, Kostas (The Greek Review of Social Research, 2020)
The article presents some preliminary findings from a survey on conspiracy beliefs among social media users in Greece. The participants were invited to complete a web survey via announcements and advertisements on social media, and the data were weighted using a reference sample from a nationally representative telephone survey. The results show that the foremost explanatory factor of conspiracy beliefs about the novel coronavirus is the acceptance of conspiracy beliefs about entirely different topics (e.g. the Greek financial crisis). The results point to the deep psychological roots of conspiracy beliefs with important implications for the design of policies in the battle against misinformation.